1994
DOI: 10.1002/art.1780370113
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Antibodies to Native or Denatured 60‐kd or 52‐kd Ro/SS‐A Proteins in Sjögren's Syndrome

Abstract: Objective. To evaluate the clinical significance of antibodies to native or denatured (anti‐n or anti‐d) 60‐or 52‐kd Ro/SS‐A proteins (60K or 52K) in Sjögren's syndrome (SS). Methods. The presence of antibodies to denatured and native Ro/SS‐A proteins was determined by immunoblotting and immunoprecipitation, respectively. Salivary gland dysfunction was evaluated by salivary function scintigraphy. Results. The incidence of anti—d‐60K without anti—d‐52K was lower among patients with systemic lupus erythematosus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 12 publications
3
19
0
Order By: Relevance
“…The remaining 16 were very weak or negative (data not shown), presumably because they contained Abs at levels below the threshold for detection by immunoblotting or that were directed against conformational epitopes, which were lost when the Ag was subjected to SDS-PAGE. The presence of Abs directed against conformational epitopes is common in other autoantigen systems (40,41). ELISA-negative sera were very weak or negative when rescreened by immunoblotting (Fig.…”
Section: Rescreening and Determination Of Subunit Specificity By Immumentioning
confidence: 92%
“…The remaining 16 were very weak or negative (data not shown), presumably because they contained Abs at levels below the threshold for detection by immunoblotting or that were directed against conformational epitopes, which were lost when the Ag was subjected to SDS-PAGE. The presence of Abs directed against conformational epitopes is common in other autoantigen systems (40,41). ELISA-negative sera were very weak or negative when rescreened by immunoblotting (Fig.…”
Section: Rescreening and Determination Of Subunit Specificity By Immumentioning
confidence: 92%
“…Serum levels of IgM were significantly correlated with those of sFas/ APO-1 in 1 ~ SS patients (r 2 = 0.632, p=0.002). It has been reported that levels of IgM are higher in sera from 1 ~ SS patients with extraglandular diseases such as pulmonary fibrosis [22]. The level of sFas/APO-1 was thus compared between extraglandular disease-positive and -negative groups.…”
Section: Relationship Between Sfas/apo-1 and Various Laboratory Parammentioning
confidence: 99%
“…The most common assays used in clinical practice to detect autoantibodies are DID and ELISA using recombinant or native proteins. Because autoantibodies most frequently target conformational determinants on native proteins and RNP particles [1,[14][15][16], the most sensitive and specific assay for the detection of autoantibodies targeting RNP particles remains IPP of cell extracts followed by visualization of the precipitated RNAs or proteins in denaturing polyacrylamide gels [15]. However, the reliability of IPP is offset by its tediousness and poor quantification.…”
Section: Discussionmentioning
confidence: 99%